Fábrica de massas alimentícias José Pappalardo : um imigrante italiano em Porto Alegre (1932 - 1968) - Ambiedo, Fernanda Trentini (2018)
This paper’s objective is to comprehend the connections of domestic entrepreneurship of Italian immigrants, focusing on the pasta factory of the family Pappalardo, which lasted for approximately 34 years between the 1930’s and the 1960’s in the city of Porto Alegre. Furthermore, it intends to contribute to a better comprehension of the importance of the family business formations of the Italian immigrants and their connections with their city, attempting to understand the formation of a local company without external investments, and with the goal of helping to build the history of the cultural influences brought with the immigrants and their culinary practices. It wants to contextualize and understand the transformations which were made during the operating period of the pasta factory, also analyzing the methods of advertisement used during that time, and the way with which they attracted the customers, as well as the rotation of employees inside the company. Finally, it is going to use the definitions of transnationalism in commercial sectors. The sources are available in the private family collection of the “Massas Pappalardo” company founder and also present in the archives of “Junta Comercial de Porto Alegre”.